Googology Wiki
Googology Wiki
(a < b)
No edit summary
(15 intermediate revisions by 11 users not shown)
Line 1: Line 1:
'''Multiexpansion '''refers to the function \(a\ \{\{2\}\}\ b = \{a,b,2,2\} = \underbrace{a \{\{1\}\} a \{\{1\}\} \ldots \{\{1\}\} a \{\{1\}\} a}_{\text{b a's}}\), using [[BEAF]].<ref>[http://www.polytope.net/hedrondude/array.htm]</ref> Or ''a'' [[Expansion|expanded]] to ''a'' for ''b'' times. They are solved backwards.
+
'''Multiexpansion '''refers to the binary function \(a \{\{2\}\} b = \{a,b,2,2\} = \underbrace{a \{\{1\}\} a \{\{1\}\} \ldots \{\{1\}\} a \{\{1\}\} a}_{\text{b a's}}\) using [[BEAF]].<ref>[http://www.polytope.net/hedrondude/array.htm Array Notation by Jonathan Bowers]</ref>
   
In the [[fast-growing hierarchy]], \(f_{\omega+2}(n)\) corresponds to multiexpandal growth rate.
+
In the [[fast-growing hierarchy]], \(f_{\omega+2}(n)\) is comparable to multiexpandal growth rate, which means multiexpansion is comparable to \(a\rightarrow a\rightarrow b\rightarrow 3\) in [[Chained Arrow Notation]] and \((a\{3,3\}b)\) in [[Notation Array Notation]].
   
 
==Examples==
 
==Examples==
   
*{a,3,2,2} = <nowiki>a{{1}}a{{1}}a</nowiki>. This is equal to ''a'' expanded to (''a'' expanded to ''a''). Let A = a{a{a...a{a{a}a}a...a}a}a (a a's), then {a,3,2,2} = a{a...a{a}a...a}a (A a's)
+
*\(\{a,3,2,2\} = a\{\{1\}\}a\{\{1\}\}a\). This is equal to ''a'' expanded to (''a'' expanded to ''a''). Let \(A = a\{a\{a...a\{a\{a\}a\}a...a\}a\}a (a\ a's)\), then \(\{a,3,2,2\} = a\{a...a\{a\}a...a\}a (A\ a's)\)
*{3,2,2,2} = <nowiki>3{{2}}2 = 3{{1}}3</nowiki> = {3,3,1,2}
+
*\(\{3,2,2,2\} = 3\{\{2\}\}2 = 3\{\{1\}\}3 = \{3,3,1,2\}\)
*{4,2,2,2} = {4,4,1,2}
+
*\(\{4,2,2,2\} = \{4,4,1,2\}\)
*{3,3,2,2} = <nowiki>3{{2}}3 = 3{{1}}3{{1}}3</nowiki> = {3,{3,3,1,2},1,2}
+
*\(\{3,3,2,2\} = 3\{\{2\}\}3 = 3\{\{1\}\}3\{\{1\}\}3 = \{3,\{3,3,1,2\},1,2\}\)
*{4,3,2,2} = {4,{4,4,1,2},1,2}
+
*\(\{6,4,2,2\} = 6\{\{2\}\}4 = 6\{\{1\}\}6\{\{1\}\}6\{\{1\}\}6 = \{6,\{6,\{6,6,1,2\},1,2\},1,2\}\)
   
 
== Pseudocode ==
 
== Pseudocode ==
Line 38: Line 38:
   
 
== See also ==
 
== See also ==
{{wedges|expansion|powerexpansion|nodot = 1}}
 
 
{{ExtendedOps}}
 
{{ExtendedOps}}
  +
[[ja:乗算膨張]]
  +
[[zh:Multiexpansion]]
 
[[Category:Functions]]
 
[[Category:Functions]]
 
[[Category:Binary operators]]
 
[[Category:Binary operators]]
  +
[[Category:BEAF]]
  +
[[Category:Jonathan Bowers]]
  +
[[Category:Extended hyper operators]]

Revision as of 00:51, 28 November 2020

Multiexpansion refers to the binary function \(a \{\{2\}\} b = \{a,b,2,2\} = \underbrace{a \{\{1\}\} a \{\{1\}\} \ldots \{\{1\}\} a \{\{1\}\} a}_{\text{b a's}}\) using BEAF.[1]

In the fast-growing hierarchy, \(f_{\omega+2}(n)\) is comparable to multiexpandal growth rate, which means multiexpansion is comparable to \(a\rightarrow a\rightarrow b\rightarrow 3\) in Chained Arrow Notation and \((a\{3,3\}b)\) in Notation Array Notation.

Examples

  • \(\{a,3,2,2\} = a\{\{1\}\}a\{\{1\}\}a\). This is equal to a expanded to (a expanded to a). Let \(A = a\{a\{a...a\{a\{a\}a\}a...a\}a\}a (a\ a's)\), then \(\{a,3,2,2\} = a\{a...a\{a\}a...a\}a (A\ a's)\)
  • \(\{3,2,2,2\} = 3\{\{2\}\}2 = 3\{\{1\}\}3 = \{3,3,1,2\}\)
  • \(\{4,2,2,2\} = \{4,4,1,2\}\)
  • \(\{3,3,2,2\} = 3\{\{2\}\}3 = 3\{\{1\}\}3\{\{1\}\}3 = \{3,\{3,3,1,2\},1,2\}\)
  • \(\{6,4,2,2\} = 6\{\{2\}\}4 = 6\{\{1\}\}6\{\{1\}\}6\{\{1\}\}6 = \{6,\{6,\{6,6,1,2\},1,2\},1,2\}\)

Pseudocode

Below is an example of pseudocode for multiexpansion.

function multiexpansion(a, b):
    result := a
    repeat b - 1 times:
        result := expansion(a, result)
    return result

function expansion(a, b):
    result := a
    repeat b - 1 times:
        result := hyper(a, a, result + 2)
    return result

function hyper(a, b, n):
    if n = 1:
        return a + b
    result := a
    repeat b - 1 times:
        result := hyper(a, result, n - 1)
    return result

Sources

See also